Proses Pembuatan Abstrak Artikel DAlam Buletin Terbitan Balai Riset dan Standarisasi Industri Padang - Mardani, Depi; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper aims to describe the writing process of bulletins rticle abstract publshed by Baristand Industry Padang. The method used in this research is descriptive. Was obtained from the literature, Baristand IndustriPadang has published the bulletinssince 1993-2011, a total of 44 series. The abstractwas extreted from the year 2007-2011, a total of 5 series in which there are 36 titles of articles. The steps of abstract extracting process, were: (1)bulletinscollecting, (2) bulletinsselecting, (3) articlesreading, (4) important information containing in the article, (5) rough draft of the records created in the previous stepcreating, (6) rough draftexamining, (7), abstracts editing (8) abstracts typing, (9) prepare an abstracts sorting, (10) index of a collection of abstractcreating. After the process completed, abstract was in one volume. Keywords: abstract of the article; Baristand Industry Padang; the process of making abstract